Acute abdomen in children: a continuous challenge. Two cases report: Meckel's Diverticulum with Small Bowel Volvolus and Internal Herniation related to Epiploic Appendagitis mimicking acute appendicitis - M. Gasparella; M. Ferro; M. Marzaro; C. Benetton; C. Zanatta; F. Zoppellaro (PAGEPress Publications, 2014)
Acute abdomen is a continuous clinical challenge in pediatric age. The aim of our study is to describe two pediatric rare cases: the first case is a small bowel volvolus related to Meckel's diverticulum confused with an intestinal intussusception; the second an internal herniation related to epiploic appendagitis with intestinal obstruction mimic acute appendicitis in two years old children. We review the current literature. Keywords: Pediatric, Caecal appendagitis, appendices epiploicae, acute abdomen, Meckel's Diverticulum, Small Bowel Obstruction, Volvolus, Internal hernia, Appendicitis.